REDUCING WATER ENTRY IMPACT LOADS ON MARINE STRUCTURES BY SURFACE MODIFICATION - Guzel, Bulent; Korkmaz, Fatih Cuneyd (UNIV ZAGREB FAC MECHANICAL ENGINEERING & NAVAL ARCHITECTURE, 2020)
In this study, the effect of hydrophobicity in reducing the impact forces during the water entry of complex geometries has been demonstrated on bow flare slamming and wet deck slamming. Superhydrophobic surfaces with a contact angle of 160 degrees and a hysteresis of 3 degrees which shows a wetting regime in the Cassie-Baxter state were obtained via a chemical coating. By conducting drop tests with a bow flare ship section model and a catamaran section model at various impact velocities, jet flows, water pileups and air cavities were compared between the hydrophilic and hydrophobic cases via high speed camera images. The impact loads acting on the test bodies under hydrophobic effects were also compared via strain gauge measurements. The rise time of the strain values was measured shorter with smaller magnitudes in the hydrophobic cases. The modification in the jet flow propagation affects the total impact force. The results showed that hydrophobicity modifies the water uprising characteristics and energy balances, and reduces the impact loads acting on marine structures during slamming events.
Keywords: Hydrophobic; water entry; slamming; impact force; bow flare; wet deck; SPHERES; MODEL; Engineering